Diclofenac inhibited the biological phosphorus removal: Performance and mechanism. (March 2020) - Zhao, Jianwei; Xin, Mingxue; Zhang, Jing; Sun, Yingjie; Luo, Siyi; Wang, Huawei; Wang, Yanan; Bi, Xuejun
Abstract: This work aims to evaluate the effect of new contaminant diclofenac (DCF) in sewage on the performance of Enhanced Biological Phosphorus Removal (EBPR) and its mechanism. The results showed that low-level DCF had no significant effect on EBPR. However, when the concentration of DCF was 2.0 mg/L, the removal efficiencies of chemical oxygen demand (COD), NH4 + -N and soluble orthophosphate (SOP) decreased significantly to 71.2 ± 4.2%, 78.6 ± 2.9%, and 64.3 ± 4.2%, respectively. Mechanisms revealed that DCF promoted the ratio of protein to polysaccharide in activated sludge extracellular polymers and inhibited anaerobic phosphorus release and oxic phosphorus uptake. Intracellular polymer analysis showed that when the DCF content was 2.0 mg/L, the maximum content of polyhydroxyalkanoates (PHA) was only 2.5 ± 0.4 mmol-C/g VSS, which was significantly lower than that in the blank. Analysis of key enzyme activities indicated that the presence of DCF reduced the activities of exopolyphosphatase and polyphosphate kinase. Graphical abstract: Image 1 Highlights: DCF inhibited nutrient removal from EBPR systems. DCF inhibited anaerobic phosphorus release and oxic phosphorus uptake. DCF reduced the relative abundance of PAO but increased the relative abundance of GAO.